2017
DOI: 10.1007/s11524-017-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Independent Effects of Neighborhood Poverty and Psychosocial Stress on Obesity Over Time

Abstract: The objective of the study was to examine the independent effects of neighborhood poverty and psychosocial stress on increases in central adiposity over time. Data are from a community sample of 157 Non-Hispanic Black, Non-Hispanic White, and Hispanic adults collected in 2002-2003 and 2007-2008, and from the 2000 Decennial Census. The dependent variable was waist circumference. Independent variables included neighborhood poverty, perceived neighborhood physical environment, family stress, safety stress, everyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…Poverty is a key neighborhood characteristic that has recently received increased attention in efforts to establish the relationship between neighborhood and obesity [ 24 , 34 – 36 ]. Neighborhood poverty may impact obesity via two potential pathways [ 37 ]. The first and most commonly recognized pathway is via unhealthy neighborhood conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Retrieved 2019-06-01 ). Obesity and PS often inhabit the same individual, owing to the Western society lifestyle [5,6]. Yet, very often, they are modeled separately, precluding a full grasp of their potentially adverse synergy on organ or system function, as well as of a deeper understanding of the disease mechanisms triggered by these concomitant stressors.…”
Section: Introductionmentioning
confidence: 99%